Cartografia das relações de saber-poder no discurso sobre ciência no Brasil no início do século 21 - Almeida, Diélen dos Reis Borges (2025)
This research is theoretically and methodologically situated within the field of Foucauldian Discourse Studies and is connected to investigations on public communication, scientific dissemination and the public perception of science. The main goal is to map, in distinct discursive levels, knowledge/power relations in the discourses on science in Brazil in the first decades of the 21st century. The specific objectives are: to investigate diffuse points of power and resistance in regards of its conditions of possibility on/of history for the emergence, debate and circulation of the concept of science in the country; to analyze how discursive subjects on public communication of science are constituted; to examine what is in conflict on truth effects on science in different say-ability instances; and to collaborate with the interface and the dialogues between linguistics studies and communication sciences. In this thesis, “science” is taken as a reference point for discourse, constituted on the act of saying, according to the historical possibilities of emergence and delimitation. The analytical archive’s constitution takes into consideration the role that statements take on the knowledge/power network of science. From three separate discursive events — government policies for sciences (implementations and/or cuts); the emergence of content on scientific dissemination; and the propagation of fake news and scientific denialism — and considering the associated field that is constructed from them, it is observed how say-abilities and visibilities are formed through/in the following instances of knowledge/power: researchers, research institutes and scientific societies; journalists and media vehicles; political authorities; and society. The analysis of the corpus composed of political statements, journalistic articles, event topics, public communication actions, posters and social media publications shows discourses on science as a condition to develop the country — at times it is talked about an economic progress, other times social progress, including the democratization of access to science — in a viewpoint rather tangled with neoliberal rationality; as well as discourses about science as an authority to create and say what is truthful, or not, about various areas of life. However, science dissemination discourse can be an act of resistance to the business model of science. Therefore, the following thesis is presented: in the first decades of the 21st century, science in Brazil is the result of knowledge/power relations, it has to serve the purpose of progress, it constructs truths for subjects’ conducts and it is, in itself, object of conflicts over what constitutes the true statement. These observations possibly extend to other times and territories.